AFFECTIVE LINKS WITH THE ASSETS OF THE BROTHERHOODS - Cordero-Fernández, Macarena (Revista de Historia Social y de las Mentalidades, 2024)
This article analyzes how objects and images – the records - gave material and emotional meaning to the existence of a brotherhood; how the links between the associates were produced through the images and goods that belonged to their corporation, and how these symbolic relations were the ones that motivated the protection and defense of the common goods. In order to do so, the article also analyzes, from the list of goods the brotherhoods, the linkages and production that these materialities generate in the devotions of their members, as well as with their group identity systems. Analysis that focuses on social psychology and sociology to observe affectivity and devotion from a perspective that goes beyond religion.
Keywords: Brotheroods; Devotion; Materiality; Identity